2021
DOI: 10.1186/s12917-021-02963-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of vitamin E and/or selenium dietary supplementation on growth parameters and expression levels of the growth-related genes in broilers

Abstract: Background Broilers are continuously stressed because of the rapid growth rate and the environmental issues associated with industrialized poultry production systems, which lead to higher susceptibility for infection with pathogens. It is well known that vitamin E (Vit. E) and selenium (Se) supplementation have protective functions in such stressful conditions. This protocol was to investigate the impact of Vit. E and/or Se on the production performance, some serum biochemistry, and expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
2
15
0
1
Order By: Relevance
“…In this study, the antibody titer against the NDV showed a nonsignificant difference between the control and treated groups. Similarly, in Abed and Ezzat (2021) and Khalifa et al (2021), no significant differences among different groups given nano-and ZnO NPs for NDV disease were found (P ≤ 0.05). In contrast, the authors in Khajarern et al (2002) have indicated that high levels of Zn supplementation (75 vs. 175 mg/kg) have led to a high antibody titer for NDV disease and IB.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In this study, the antibody titer against the NDV showed a nonsignificant difference between the control and treated groups. Similarly, in Abed and Ezzat (2021) and Khalifa et al (2021), no significant differences among different groups given nano-and ZnO NPs for NDV disease were found (P ≤ 0.05). In contrast, the authors in Khajarern et al (2002) have indicated that high levels of Zn supplementation (75 vs. 175 mg/kg) have led to a high antibody titer for NDV disease and IB.…”
Section: Discussionmentioning
confidence: 83%
“…These lesions could be attributed to oxidative stress and the upregulations in gene expression of IL1α and TNF-α. This correlated increment in ROS production and inflammatory cytokines can diminish the mitochondrial function within cells (Hussain et al 2005 ; Khalifa et al 2021 ; Xia et al 2006 ), leading to moderate to severe damage in the internal morphology of different organs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, selenium is required for GPx, which transforms H 2 O 2 and lipid hydroperoxides into alcohols [ 21 , 22 ]. Vitamin E and selenium, in particular their antioxidant and immune functions, can work together to influence biological processes [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few clinical trials have been carried out to study the effect of selenium in combination with vitamin E alone. However, there is a multitude of studies on this specific combination in animals, such as rats or chickens [ 158 , 159 , 160 , 161 ].…”
Section: Nutritional Factors Interfering With the Effects Of Vitamin ...mentioning
confidence: 99%